2015
DOI: 10.1155/2015/650431
|View full text |Cite
|
Sign up to set email alerts
|

Development of Activity-Related Muscle Fatigue during Robot-Mediated Upper Limb Rehabilitation Training in Persons with Multiple Sclerosis: A Pilot Trial

Abstract: Robot-assisted rehabilitation facilitates high-intensity training of the impaired upper limb in neurological rehabilitation. It has been clinically observed that persons with Multiple Sclerosis (MS) have difficulties in sustaining the training intensity during a session due to the development of activity-related muscle fatigue. An experimental observational pilot study was conducted to examine whether or not the muscle fatigue develops in MS patients during one session of robot-assisted training within a virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
0
24
1
Order By: Relevance
“…Although several pharmacological treatments are available to control MS symptoms, assessments and rehabilitation using physical therapies have proven to help improve the quality of life [102]. Fatigue is an important factor to consider during rehabilitation and in designing rehabilitation plans [103], as studies have shown a decline in performance during rehabilitation tasks due to fatigue [104,105]. In this section, we discuss several techniques investigated by researchers for monitoring and detecting fatigue during rehabilitation.…”
Section: Measuring and Analyzing Fatigue In Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several pharmacological treatments are available to control MS symptoms, assessments and rehabilitation using physical therapies have proven to help improve the quality of life [102]. Fatigue is an important factor to consider during rehabilitation and in designing rehabilitation plans [103], as studies have shown a decline in performance during rehabilitation tasks due to fatigue [104,105]. In this section, we discuss several techniques investigated by researchers for monitoring and detecting fatigue during rehabilitation.…”
Section: Measuring and Analyzing Fatigue In Rehabilitationmentioning
confidence: 99%
“…Octavia et al evaluated muscle fatigue during robot-mediated upper limb rehabilitation as PwMS and healthy control subjects were performing five sessions of lifting and transporting exercises using a HapticMaster robot and an I-Travel system [104]. While performing the tasks EMG was recorded from the anterior deltoid and trapezius muscles, filtered using Infinite Impulse Response and Butterworth bandpass filters and then rectified using an RMS sliding window approach.…”
Section: Measuring and Analyzing Fatigue In Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this prospective cohort study, pwMS attended 5 training sessions per 2 weeks, alternating 3 [32] whereas 8 weeks of training is often applied in MS [26][27][28]30]. In pwMS with overall high disability, a more extensive but more time-spread training program was required taking into account the occurrence of activity-related motor fatigue and higher risk for training overload [24].…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…However, it is still not clear whether (robot-mediated) upper limb training is successful in pwMS to the same extent as stroke patients, due to progressive neurodegeneration and presence of motor fatigue potentially interfering with feasible training intensity [24,25]. As in stroke, new training technologies, focusing on robotic and/or sensor-based technology, are being developed to improve upper limb movement in pwMS and indications for improvement were found in previous studies [26][27][28].…”
mentioning
confidence: 99%